Strategy for Change Agent Driving towards Strong Community Building under the Context of Urban Community in Metropolitan Area - Raweethanathorn, Nattapakorn; Sirisunhirun, Somboon (Journal of Management Science Nakhon Pathom Rajabhat University, 2023)
The objectives of this research were 1) to study the components affecting the change agent driving; 2) to study the environment data that related to the change agent driving; and 3) to analyze and formulate a strategy for driving change agent towards strong community building under the context of urban community. The mixed-methodology was conducted in this research, the sample groups and key informants used in this research consisted of 1) community leaders who have participated in the strengthening and developing change agent project; and 2) stakeholders in the area or nearby communities. The quantitative research was conducted by questionnaire from 162 samples. The qualitative research was conducted by in-depth interview and focus group discussion from 84 key informants. This research analyzed data by descriptive statistics, stepwise linear multiple regression analysis, content analysis, and SWOT analysis. The results revealed that four components consisted of Transformational Leadership; Networking; Food Security; and Community Management had affected to the change agent driving towards building strong communities. Also, the study found important findings as follows: 1) participation enhancement; 2) food security building; 3) network integration; 4) “Leader must do first” conduction; 5) people encouragement; 6) social adaptation; 7) next generation leader promotion; 8) public awareness; 9) thought leader searching; and 10) community fund seeking. These findings used for formulating strategies in 4 aspects as follows: 1) integrating workspaces 2) founding support systems 3) enhancing leader capabilities and 4) creating innovations for community driving. The important recommendations are as follows: 1) emphasize on networking to operation support; 2) adapt the activity according to various situations and social land scapes; and 3) strategies or innovative model should be applied for driving change agents to cover all areas widely. Article history: Received 27 October 2022 Revised 14 June 2023 Accepted 19 June 2023 SIMILARITY INDEX = 4.87 %